An Analysis Of Stunting Incidence In Indramayu District - Yulyanti, Depi; Dedeh Husnaniyah; Rudiansyah (Journal of Global Research in Public Health, 2019)
Health and nutrition development policies for the period 2015-2019 / Perpres No.2 / 2015 are focused on reducing the prevalence of stunting. Stunting problems are influenced by the condition of the mother, fetus, baby, including illnesses suffered during infancy and other conditions that affect health. The government targets in 2019 the prevalence of stunting in children under 2 years must decrease to 28% of cases that occur in Indonesia. This study aims to analyze the incidence of stunting in Indramayu Regency. This study uses a quantitative research design with cross sectional approach. Research variables include genetic , prenatal, postnatal , environmental sanitation, and personal hygiene variables in Indramayu Regency. The population in this study were mothers who had stunting children in the working area of ​​the Kandanghaur Community Health Center in Indramayu District, while the sample of this study was 308 people. The instruments used were questionnaire sheets and observation sheets . Analysis of the data used is univariate analysis. Based on the results of measurements returned to a sample of 308 children who had been declared stunted it was known that there were only 119 children who were declared stunting. This happens because there are errors in measurement during posyandu activities, measurement results at posyandu are not well documented so the reported data does not match the data in the field. The conclusion in this study is that the high number of stunting is not entirely caused by cases in the field, but errors in measurement and reporting are the main contribution in increasing the stunting level. It is necessary to conduct training on posyandu management for posyandu facilitators.